1999
DOI: 10.1007/s004120050359
|View full text |Cite
|
Sign up to set email alerts
|

The degradation profile of extrachromosomal circular DNA during cisplatin-induced apoptosis is consistent with preferential cleavage at matrix attachment regions

Abstract: Extrachromosomal circular DNA molecules are prevalent in cancer cells and harbor amplified genes, such as oncogenes and drug resistance genes, that can provide a selective growth advantage to cancer cells. These circular DNA structures include double minute chromosomes (dmin), which can be detected with light microscopy following Giemsa staining, and submicroscopic circular DNA structures referred to as episomes. In this study, we investigated the fate of dmin and episomes in multidrug-resistant human epidermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…For example, sites of chromosomal breakpoints preferentially localize to MARs [Schoenlein et al, 1999] and aberrant binding of DNA to the nuclear matrix may destabilize the expression of a host of genes that maintain cells in a noncancerous state [Linnemann and Krawetz, 2009a]. In the present study, we investigated for the first time the role of MARs in the regulation of transcription of the TP53 gene domain in breast cells.…”
Section: Discussionmentioning
confidence: 96%
“…For example, sites of chromosomal breakpoints preferentially localize to MARs [Schoenlein et al, 1999] and aberrant binding of DNA to the nuclear matrix may destabilize the expression of a host of genes that maintain cells in a noncancerous state [Linnemann and Krawetz, 2009a]. In the present study, we investigated for the first time the role of MARs in the regulation of transcription of the TP53 gene domain in breast cells.…”
Section: Discussionmentioning
confidence: 96%
“…34 There have been a number of reports in the literature suggesting that initiation of apoptotic DNA cleavage occurs at matrix attachment regions. 6,7,[35][36][37] The first supporting evidence came from studies that establish that high molecular weight DNA fragments of 50 and 300 kb, produced in early stages of apoptosis, represent structural domains of chromatin, loops and rosettes, respectively. 1,7 It was then suggested that topoisomerase II, located at matrix attachment sites, is responsible for this cleavage since inhibition of its activity generated the same pattern of DNA fragments.…”
Section: Discussionmentioning
confidence: 99%
“…The cleavage sites have not been precisely mapped, due to a significant heterogeneity in MAR sequence and size as well as errors in sizing the apoptotic DNA fragments which, under the PFGE resolution, could be several kilobases. 7,36,37 Our approach was to use LM-PCR to map precisely the cleavage sites in the genomic sequences selected based on their high similarity to the SATB1-binding site sequence within the IgH gene enhancer region, their base content (i.e., A+T-rich, clustering of ATC exclusively on one strand) and location in noncoding regions of the genome. These features are considered to be characteristic for the core-unwinding element of BURs.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, total oligonucleosomal DNA obtained from 2x10 7 cells was loaded into one lane of a 2% agarose gel and subjected to conventional gel electrophoresis. To detect high molecular weight (HMW) DNA degradation, pulsed field gel electrophoresis analysis was performed as previously described (34)(35)(36). In brief, chromosomal DNA was embedded into agarose plugs and deproteinized in situ in EST lysis buffer [500 mM EDTA (pH 9.0) 1.0 % sodium lauroylsarcosine, 2 mg/ml proteinase K] (Boehringer Mannheim, Indianopolis, IN).…”
Section: Methodsmentioning
confidence: 99%